Analysis of Land Cover Distribution and Spatial Pattern of Landscape Fragmentation and Connectivity in the Taperoá and High Paraíba River Basins, Brazil - Porto de Lima, Valéria Raquel; da Silva-Seabra, Vinícius; Albuquerque-Xavier, Rafael; da Conceição-Dornellas, Patricia (Revista de Estudios Andaluces, 2019)
The Upper Paraíba and Taperoá river basin are located in the semiarid zone of Paraíba State. Much of the delimitation of the semiarid region has Caatinga forests, which, due to its bioclimatic conditions, diversity and endemism, become a singular biome, extending over a surface area of 844,453Km2 IBGE (2010). The objective of this study was to evaluate soil use and cover, spatial pattern of fragmentation and connectivity of the Upper Paraíba and Taperoá basin. The mapping was done from GEOBIA classification of MSI images of Sentinel 2 satellite, and worked on GUIDOS software. The vegetation cover and the water and bioclimatic condition of the surveyed area were used. The results point to a greater presence of caatinga areas in quantity and connectivity in the northwest of Upper Paraíba and in the southwest of Taperoá.